Comprehensive Support for Family Caregivers: Impact on Veteran Health Care Utilization and Costs. (February 2019) - Van Houtven, Courtney Harold; Smith, Valerie A.; Stechuchak, Karen M.; Shepherd-Banigan, Megan; Hastings, Susan Nicole; Maciejewski, Matthew L.; Wieland, Gilbert Darryl; Olsen, Maren K.; Miller, Katherine E. M.; Kabat, Margaret; Henius, Jennifer; Campbell-Kotler, Margaret; et al.
This study aimed to examine the early impact of the Program of Comprehensive Assistance for Family Caregivers (PCAFC) on Veteran health care utilization and costs. A pre-post cohort design including a nonequivalent control group was used to understand how Veterans' use of Veteran Affairs health care and total health care costs changed in 6-month intervals up to 3 years after PCAFC enrollment. The control group was an inverse probability of treatment weighted sample of Veterans whose caregivers applied for, but were not accepted into, PCAFC. Veterans in PCAFC had similar acute care utilization postenrollment when compared with those in the control group, but significantly greater primary, specialty, and mental health outpatient care use at least 30, and up to 36, months postenrollment. Estimated total health care costs for PCAFC Veterans were $1, 500 to $3, 400 higher per 6-month interval than for control group Veterans. PCAFC may have increased Veterans' access to care.